Treatment of Problem Behavior Multiply Maintained By Access to Tangible Items and Escape from Demands - (:unkn) unknown (My University, 2018)
Functional analysis is a behavioral assessment that identifies sources of operant reinforcement that maintain problem behavior. These assessments may identify single reinforcers (e.g., positive reinforcement in the form of attention) or multiple reinforcers (e.g., positive reinforcement in the form of attention and negative reinforcement in the form of escape from instructions) for the same behavior. In such cases, analysts will design interventions for each identified “function” but the sequencing of these interventions may impact their success at treating problem behavior. The current study evaluated the sequential treatment of problem behavior for a child whose functional analysis identified sensitivity to multiple reinforcers, similar to those described above. We first targeted problem behavior maintained by positive reinforcement in the form of access to tangible items using functional communication training (FCT). We subsequently targeted problem behavior maintained by negative reinforcement in the form of termination of instruction using Differential Reinforcement of Compliance (DRC). The implications for this intervention sequence are discussed.
Keywords: differential reinforcement; multiple control; problem behavior